2009
DOI: 10.1111/j.1365-2036.2009.04106.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the effects of concomitant medications on thiopurine metabolism in inflammatory bowel disease

Abstract: SUMMARY BackgroundThiopurines are increasingly used in the treatment of inflammatory bowel disease (IBD), being the most common immunosuppressive therapy; however, potentially harmful interactions between thiopurines and other drugs (especially 5-aminosalicylic acid, 5-ASA) were described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 53 publications
4
11
3
Order By: Relevance
“…Finally, some authors have suggested a synergistic effect of aminosalicylates or infliximab on thiopurine metabolite RBC levels 38, 39 ; we found no influence on metabolite RBC levels by any of those drugs. Even though we could not analyse the impact of different doses, our results regarding the impact of aminosalicylates on thiopurine metabolism is consistent with previous studies 8, 40 …”
Section: Discussionsupporting
confidence: 91%
“…Finally, some authors have suggested a synergistic effect of aminosalicylates or infliximab on thiopurine metabolite RBC levels 38, 39 ; we found no influence on metabolite RBC levels by any of those drugs. Even though we could not analyse the impact of different doses, our results regarding the impact of aminosalicylates on thiopurine metabolism is consistent with previous studies 8, 40 …”
Section: Discussionsupporting
confidence: 91%
“…Likewise, no differences were found in 6-thioguanine and 6-methylmercaptopurine levels between the two patient groups [Daperno et al 2009]. These results differ from those recorded in other intervention studies in which the addition of 5-ASA to stable thiopurine doses was found to significantly increase the 6-thioguanine levels [de Boer et al 2007;Gilissen et al 2005].…”
Section: Introductioncontrasting
confidence: 56%
“…Not all studies have reproduced these results. In a cross‐sectional study of 183 consecutive IBD patients no significant differences were noted in 6‐TGN or 6‐MMP levels or TPMT activity between thiopurine patients receiving, or not receiving, concomitant aminosalicylates ( P > 0.05) 41. It would seem prudent to conclude that while TPMT inhibition by aminosalicylates may occur, the clinical significance of this interaction is minimal.…”
Section: How To Optimize Thiopurine Therapy?mentioning
confidence: 92%